FEASIBILITY TEST OF AN RTL-SDR BASED DIGITAL MODULATION TRAINER IN A GUIDED INQUIRY LEARNING MODEL - Rifai, Moch.; Suprapto, Yuyun; Bagus Harianto, Bambang (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Utilization technology software defined radio with the aim of maximizing hardware to build a softwarebased radio need balanced with readiness institution education in build curriculum, syllabus and tool adequate practice. This Study aim get digital modulation practice tool or trainer based on RTL-SDR for cadet with a guided inquiry learning model and know the feasibility of trainer. With a research model development that follows Thiagarajan's 4D rules and product feasibility testing study use questionnaire material experts , media experts, and trained cadets on the Mardapi’s scale The trainer obtained a feasibility score of 85.2 which means very worthy used.